Peningkatan Kepuasan Pasien dan Keluarga Terhadap Pelayanan Keperawatan Dengan Melibatkan Keluarga Dalam Pemberian Kebutuhan Dasar di Unit Perawatan Intensif: Literature Review - Uswatun Hasanah; Ratna Sitorus; Agung Waluyo (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Intensive care unit (ICU) is an important part of the management of the disease of a hospital that handles illnesses with complex cases both acute and chronic. Various diseases that arise because these cases become a challenge for health workers to think more about how to overcome health problems that exist from the other side outside of medical treatment, one of which is by involving families to participate in treatment. Generally in intensive care units, the family is not actively involved in caring for patients in a meaningful way. The family-centered care model makes the family active in working with and participating in the care team. The purpose of this study to describe, analyze and compare the influence of family involvement in providing basic needs to patient and family satisfaction in the intensive care room. This literature review was a search of online databases such as EBSCO-host, ScienceDirect, ProQuest, SAGE. Search for articles published from 2014-2019 received 13 relevant articles. The result by involving families in care at the ICU can increase family satisfaction with nursing services. Involving families in care accompanied by nurses provides many benefits for patient recovery. Therefore, involving families in the care team at the ICU can be applied to accelerate the recovery process of patients, reduce daycare and can increase family satisfaction with the services provided. Keywords: family satisfaction; family involvement; intensive care unit; family needs